2018
DOI: 10.1111/jph.12778
|View full text |Cite
|
Sign up to set email alerts
|

Nursery treatments with resistant inducers, soil amendments and biocontrol agents for the management of the Fusarium wilt of lettuce under glasshouse and field conditions

Abstract: Lettuce Fusarium wilt, caused by Fusarium oxysporum f. sp. lactucae, represents a major problem in most lettuce production areas worldwide. In the present study, a number of resistance inducers, organic amendments and biocontrol agents were applied in a preventative way, in experimental and commercial situations, to soils artificially or naturally infested with race 1 of the pathogen, and to moderately susceptible lettuce cultivars. Potassium phosphite, acibenzolar-S-methyl, green composts, and Bacillus subtil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
1
4
0
1
Order By: Relevance
“…In addition, Trichoderma was effective against PHC, as already reported by many authors (Ahmed et al, 2000;Ezziyyani et al, 2007;Lorito et al, 2010;Bae et al, 2011). Furthermore, in a previous study carried out in field conditions (Gilardi et al, 2019), the application of Trichoderma TW2 alone against Fusarium wilt in lettuce was less effective compared to the use of CM compost, in combination with Trichoderma TW2. Bonanomi et al (2018) reviewed several works on biocontrol agents (BCAs) compost enrichment and pointed out that this could be the most promising way to achieve a long-term suppressiveness against soil-borne pathogens.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, Trichoderma was effective against PHC, as already reported by many authors (Ahmed et al, 2000;Ezziyyani et al, 2007;Lorito et al, 2010;Bae et al, 2011). Furthermore, in a previous study carried out in field conditions (Gilardi et al, 2019), the application of Trichoderma TW2 alone against Fusarium wilt in lettuce was less effective compared to the use of CM compost, in combination with Trichoderma TW2. Bonanomi et al (2018) reviewed several works on biocontrol agents (BCAs) compost enrichment and pointed out that this could be the most promising way to achieve a long-term suppressiveness against soil-borne pathogens.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, Trichoderma was effective against PHC, as already reported by many authors ( Ahmed et al, 2000 ; Ezziyyani et al, 2007 ; Lorito et al, 2010 ; Bae et al, 2011 ). Furthermore, in a previous study carried out in field conditions ( Gilardi et al, 2019 ), the application of Trichoderma TW2 alone against Fusarium wilt in lettuce was less effective compared to the use of CM compost, in combination with Trichoderma TW2.…”
Section: Discussionmentioning
confidence: 85%
“…The incidence of plant pathogens also represents a significant problem in most lettuce production areas and systems in which integrated production systems, based on accurate identification of plant pathogens and appropriate risk assessments, are required. Biocontrol agents have been applied in soils infested for disease control, but their use in practice should be integrated with other control strategies (Gilardi et al., 2019). These safety issues have to be strictly considered when designing strategies to enhance the bioactive content in lettuce using preharvest and postharvest approaches.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In the present study, B. subtilis was only able to slightly reduce the severity of wilt symptoms caused by the pathogen (22%-48% efficacy). Other studies have demonstrated the ability of B. subtilis to reduce the Fusarium wilt of lettuce, particularly when it is first applied in the nursery (Gilardi et al 2016(Gilardi et al , 2019, or as a seed dressing (Lopez-Reyes et al 2014).…”
Section: Discussionmentioning
confidence: 99%